2019
DOI: 10.18865/ed.29.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Stress Reduction in the Prevention of Left Ventricular Hypertrophy: A Randomized Controlled Trial of Transcendental Meditation and Health Education in Hypertensive African Americans

Abstract: Background: African Americans have dis­proportionately high rates of cardiovascular disease (CVD). Left ventricular hypertrophy (LVH) is an independent risk factor for CVD and may contribute to this disparity. Psycho­logical stress contributes to LVH in African Americans and other populations.Objective: This study evaluated the effects of stress reduction with the Transcendental Meditation (TM) technique on prevent­ing LVH in African American adults with hypertension.Setting: Martin Luther King Hospital - Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…The effects of Transcendental Meditation on blood pressure have also been reported . A study of 298 university students randomized to Transcendental Meditation or wait‐list control found at 3‐month follow‐up no significant changes in systolic or diastolic blood pressure, although significant reductions in blood pressure (5/3 mm Hg, respectively) did occur in those at high risk of the development of hypertension .…”
Section: Effects Of Meditation On Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of Transcendental Meditation on blood pressure have also been reported . A study of 298 university students randomized to Transcendental Meditation or wait‐list control found at 3‐month follow‐up no significant changes in systolic or diastolic blood pressure, although significant reductions in blood pressure (5/3 mm Hg, respectively) did occur in those at high risk of the development of hypertension .…”
Section: Effects Of Meditation On Blood Pressurementioning
confidence: 99%
“…A study of 298 university students randomized to Transcendental Meditation or wait‐list control found at 3‐month follow‐up no significant changes in systolic or diastolic blood pressure, although significant reductions in blood pressure (5/3 mm Hg, respectively) did occur in those at high risk of the development of hypertension . In a randomized study of stress reduction in 201 black men and women with angiographically documented coronary artery disease randomized to Transcendental Meditation or health education, 5.4‐year follow‐up found a 4.9 mm Hg lower systolic blood pressure, 1 of numerous secondary study end points, in those randomized to Transcendental Meditation than in those randomized to health education, primarily because of an increase in blood pressure in the health education group …”
Section: Effects Of Meditation On Blood Pressurementioning
confidence: 99%
“…The positive psychological results reported in the studies were reducing anxiety, depression, stress (Bakara et al, 2013;Carneiro et al, 2017;Delui, Yari, Khouyinezhad, Amini & Bayazi, 2013;Ikedo, Gangahar, Quader & Smith, 2007;Lukman, Akbar & Ibrahim, 2012;Momeni, Omidi, Raygan & Akbari, 2016a;Nyklíček, Dijksman, Lenders, Fonteijn & Koolen, 2014;Parswani, Sharma & Iyegar, 2013;Stein et al, 2010;Tacón, McComb, Caldera & Randolph, 2003;, increasing psycho-spiritual comfort (Bakar, 2017), coping (Mufarokhah, Putra & Dewi, 2016), spiritual wellbeing , and anger, confusion, fatigue (Ikedo et al, 2007) and hope . The reported positive biological parameters include stress hormones (Robert McComb, Tacon, Randolph & Caldera, 2004), hemodynamic parameters (Carneiro et al, 2017;Delui et al, 2013;Momeni et al, 2016a;Parswani et al, 2013), myocardial infarction attack and cardiac revascularization (Schneider et al, 2012) and cardiovascular function (Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, published randomized controlled trials have reported that this meditation practice, when used in conjunction with usual medical care, is associated with reductions in mortality 8 and in the composite of all-cause mortality, myocardial infarction, and stroke. 9 In light of these more recent findings, we suggest that the AHA committee update its review and recommendations on nonpharmacologic interventions for blood pressure, particularly in regard to the Transcendental Meditation technique. Patients with high blood pressure should be made aware that there is another evidence-based option for the prevention and treatment of high blood pressure that may help to mitigate the need for drug therapy.…”
mentioning
confidence: 99%